Jogos digitais e a aprendizagem do adulto: uma revisão integrativa - Jungbluth , Anna (2017)
As the digital technological development increasing since the decade of 1960 with the advent of the web / internet and its dissidents, such as the digital game development of in the 1970/1980, in constant innovation even today, the present research aims to analyze cognitive traces that suggest adult learning who play. It is understood that learning using the memories and other neurocognitive functions also for development, as the perception, abstraction, logic and imagination. The research is developed using the integrative review method that received the increment of neurocognitive categorization developed by Garrido (2005, 2012), based on Pinker (1998, 2007, 2008) and Izquierdo (2011), in the analysis phase. The results include eighteen scientific publications. It is argued that the insertion of digital games in educational practices can contribute to the significance of knowledge because there is evidence of interference in cognitive traces that sugest adult learning who play. The development of different neurocognitive functions was especially identified in correlation with more flexible, adaptable games with smooth gameplay that allow to error, greater immersion and understanding of its rules or created by participatory design; in games classified as entertainment and games made available in virtual learning environments; and identified when adult players are more interested in learning and playing. To insert the digital games in educational environments and understanding Education in the scenario of a knowledge society of the digital and virtual age, it is necessary to establish educational focus articulated with the field of Cognitive Sciences.